An Investigation of Transactions Data for NYSE Stocks - WOOD, ROBERT A.; McINISH, THOMAS H.; ORD, J. KEITH (Journal of Finance, 1985)
ABSTRACT Using transactions data, the behavior of returns and characteristics of trades at the micro level is examined. A minute‐by‐minute market return series is formed and tested for normality and autocorrelation. Evidence of differences in return distributions is found among overnight trades, trades during the first 30 minutes following the market opening, trades at the close, and trades during the remainder of the day. The latter distribution is found to be normal. Unusually high returns and standard deviations of returns are found at the beginning and the end of the trading day. When the beginning‐and end‐of‐the‐day effects are omitted, autocorrelation in the market return series is reduced substantially. A number of patterns in trading are reported.